Peran Mahasiswa Dalam Edukasi Pajak Kendaraan Bermotor Melalui Program KKN di Kabupaten Sukabumi - Abdullah, Sodiki; Nuraeni, Erni; Nisa Putri, Dhitya Auliya; Silpiana, Devi; Delia, Delia; Tazkia, Meutia; Sofiani, Venita (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
KKN is a form of student engagement aimed at contributing to society while providing experiential learning opportunities. This KKN program, conducted in Sukabumi Regency, focused on educating high school students as prospective first-time taxpayers about Motor Vehicle Tax (PKB). The implementation methods included direct socialization, hands-on practice using the Sapawarga application for digital PKB payments, and education on the role of Jasa Raharja in road user protection. The results indicated a significant improvement in participants’ understanding of PKB’s function as a source of regional revenue (PAD), the proper tax payment procedures, and the importance of timely tax compliance. Furthermore, practical training on the Sapawarga application effectively enhanced participants’ digital literacy and reduced technological barriers. This program also emphasized the importance of synergy between universities, government agencies (SAMSAT), and the community in fostering a healthy tax ecosystem. Overall, this KKN successfully instilled early tax awareness, supported the digital transformation of public services, and encouraged the formation of a tax-conscious, technologically literate young generation that actively contributes to regional development.